2009
DOI: 10.1080/14680629.2009.9690240
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Bituminous Mixtures Blended with Second Reclaimed Asphalt Pavements (R2AP)

Abstract: Reclaimed asphalt pavements (RAP) have been called one of the most recycled materials in the world. Pavements mixed with RAP would be milled or excavated when they reach the end of service life. The reuse of RAP makes it as a second RAP, and is referred as R 2 AP in this study. R 2 AP was added at ten levels to hot-mix asphalt mixtures (HMA) with four different recycling agents in the laboratory. Adding 40% R 2 AP did not appear to alter the mixture properties dramatically. When the percentage was higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…Widyatmoko [6], used three different levels of addition of RAP (10%, 30% and 50% Recent researches [1][2][3][4][5][6][7][8][9][10], have established that RAP replacement at proportions above 50% is feasible to produce new HMA mixtures, obtaining satisfactory results in the mechanical properties. It is universally recognized that an important benefit of asphalt as a pavement construction material is its ability to be recycled.…”
Section: Literaturementioning
confidence: 99%
“…Widyatmoko [6], used three different levels of addition of RAP (10%, 30% and 50% Recent researches [1][2][3][4][5][6][7][8][9][10], have established that RAP replacement at proportions above 50% is feasible to produce new HMA mixtures, obtaining satisfactory results in the mechanical properties. It is universally recognized that an important benefit of asphalt as a pavement construction material is its ability to be recycled.…”
Section: Literaturementioning
confidence: 99%
“…It is seen from several studies that there are many commercial rejuvenators are available in the market which showed promising results. However, the cost of the commercial products is very high and that will increase the overall pavement construction cost, which will confront the usage of RAP [8]. To overcome those issues in this study, non-commercial rejuvenator is used.…”
Section: Introductionmentioning
confidence: 99%
“…RAP is considered to be one of the most important types of green asphalt pavement that minimizes environmental impacts through the reduction of energy consumption, natural resources and associated emissions while meeting all performance conditions and standards. In pursuit of sustainable development principles, sustainable development is defined as meeting the needs of the present without compromising the ability of future generations to meet their own needs [9] [11].…”
Section: Reclaimed Asphalt Pavementmentioning
confidence: 99%